A finite–strain elastoplasticity material model for ETFE membrane structures. (June 2019) - Coelho, Marianna; Roehl, Deane
Highlights: Numerical model to simulate membrane structures of ETFE. Constitutive material model considering elastoplastic behaviour with von Mises hardening criteria law. Comparison of constitutive elastoplastic material model with small, large strains and experimental data. Examples: uniaxial, biaxial and burst test. Abstract: This work presents a numerical model for the simulation of the behavior of membrane structures fabricated using ethylene tetrafluoroethylene (ETFE) materials. The elastoplastic material model with von Mises yield criteria is considered in the numerical analysis. Small strain and large strain formulation were adopted for comparison. The model simulates material tests, uniaxial and biaxial, and a burst test, for which experimental measurements are available. The use of von Mises yield criteria is suggested for ETFE foils. The results obtained with the numerical analysis with large strains are in accordance with the experimental results. On the other hand, the results of the numerical analysis with small strains are valid only in the first few steps of the analysis. These results reinforce the importance of considering a material model with large strains to model this type of material.